Preparation method of ionic liquid functionalized Silicalite-1-coated SiO2 mixed matrix membrane

Through the preparation method of ionic liquid functionalized Silicalite-1@SiO2 hybrid matrix membrane, the existing CO2 separation technology has solved the problems of high energy consumption and low selectivity in low concentration CO2 environments, and achieved efficient CO2 separation performance.

CN119499885AActive Publication Date: 2025-02-25DALIAN UNIV OF TECH PANJIN INST OF IND TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411825656.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing CO2 separation technology has high energy consumption and is expensive in low-concentration CO2 environments, and the membrane material has low permeability and selectivity to CO2/N2, making it difficult to effectively separate CO2.

Method used

The mixed matrix membrane of ionic liquid was used to function the Silicalite-1@SiO2@SiO2 nanoparticle filler of ionic liquid was mixed with the Pebax-1657 solution to form a uniform cast film liquid, and the mixed matrix membrane was prepared by solvent evaporation.

Benefits of technology

The dissolution selectivity of membrane materials to CO2 gas is improved, the CO2 permeability can reach 83.43~115.64Barrer, and the CO2/N2 selectivity reaches 57.24~78.28, significantly improving the CO2 separation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499885A_ABST
    Figure CN119499885A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas separation materials, in particular to a preparation method of an ionic liquid functionalized Silicalite-1-coated SiO2 mixed matrix membrane. The problems of low CO2 / N2 permeability and selectivity and poor interfacial compatibility of the membrane material are solved by preparing the porous ionic liquid loaded Silicalite-1-coated SiO2 filler with large specific surface area and CO2 adsorption performance. The high specific surface area of the Silicalite-1-coated SiO2 nanoparticles provides abundant active sites, enhances the gas adsorption capacity, and improves the separation efficiency. According to the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, dissolution and adsorption of CO2 are enhanced through physical adsorption, and selective capture of CO2 is promoted through the strong van der Waals action of anions of the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate and CO2 molecules. The surface functionalization of Silicalite-1-coated SiO2 improves the selectivity of CO2 / N2, and also can adjust the interaction force with CO2, thereby improving the separation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas separation materials, in particular to a method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane. Background Art

[0002] CO2 is one of the most pressing environmental issues facing humanity today, as global climate change is one of the main components of greenhouse gases. The substantial increase in its emissions has led to an increase in the Earth's temperature, which in turn has triggered a series of environmental problems such as extreme weather and rising sea levels. According to the report of the United Nations Intergovernmental Panel on Climate Change (IPCC), significant reductions in CO2 emissions must be achieved in the next few decades to avoid serious climate consequences. Therefore, CO2 gas separation technology has become one of the key means to achieve this goal.

[0003] Current CO2 separation technologies, including chemical adsorption and physical adsorption, generally have the problems of high energy consumption and high cost. Especially in low-concentration CO2 environments (such as air), separating and capturing CO2 requires more energy input, so it is crucial to find efficient and economical separation methods. Membrane separation technology, with its advantages of high efficiency, environmental protection, easy operation and low cost, is gradually replacing some traditional separation technologies and becoming an indispensable separation method in modern industry.

[0004] With the continuous development of CO2 separation membranes, membrane materials have also been carefully studied and found that both polymers and inorganic materials have their own advantages and disadvantages. Among them, polymers are easy to form membranes and have stable chemical structures, but their anti-aging and plasticization properties are poor, which will affect the separation performance of the membrane; while inorganic materials are difficult to form membranes and process, brittle, and high in cost, which seriously restricts development. In the field of gas separation membrane research, the most typical trade-off effect is the balance between permeability and selectivity. As permeability increases, selectivity tends to decrease; as selectivity increases, permeability tends to decrease; the trade-off effect limits the separation performance and application of the membrane; however, MMMs are a composite membrane composed of a polymer matrix and an inorganic filler, which aims to combine the advantages of polymer membranes and inorganic membranes, take advantage of their strengths and avoid their weaknesses, and achieve better separation performance; mixed matrix membranes combine the advantages of polymers and inorganic materials, showing good gas selectivity, high temperature resistance and chemical corrosion resistance, and cost-effectiveness, and are particularly suitable for industrial applications such as gas separation, liquid purification, and wastewater treatment. By optimizing the type, size and distribution of inorganic fillers, as well as the compatibility of the polymer matrix, the separation performance of mixed matrix membranes can be further improved, becoming an important direction for the future development of separation technology. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane, wherein the method comprises mixing the prepared ionic liquid functionalized Silicalite-1@SiO2 nanoparticle filler with a Pebax-1657 solution to form a uniform casting solution, and then preparing the mixed matrix membrane by a solvent evaporation method. The ionic liquid functionalized Silicalite-1@SiO2 nanoparticle filler is a high-performance composite material that combines the MFI structure of the molecular sieve Silicalite-1, the stability of silica and the functionality of the ionic liquid. This nanoparticle filler has unique chemical properties. Due to its large specific surface area and high surface energy, the material has extremely high chemical activity. Specifically, Silicalite-1@SiO2, as a carrier, can increase the loading amount of the ionic liquid, which is particularly important when preparing the mixed matrix membrane. The addition of the ionic liquid not only greatly promotes the compatibility of Silicalite-1@SiO2 with the polymer matrix, but also the functional groups in the ionic liquid increase the selectivity for CO2, which is crucial to improving the performance of the mixed matrix membrane. In addition, the dispersibility of IL-functionalized Silicalite-1@SiO2 nanoparticles in non-polar solvents is significantly improved, which not only facilitates the preparation of membranes but also avoids filler agglomeration, thereby improving the uniform dispersion of fillers in mixed matrix membranes. This uniform dispersion is critical to ensure the performance consistency of the membrane and optimize its separation efficiency. The introduction of ionic liquids not only enhances the hydrophilicity and thermal stability of the nanoparticles, but also improves their adsorption selectivity for specific gas molecules. Therefore, the addition of Silicalite-1@SiO2 and the functionalization of ionic liquids together provide a series of advantages for the composite material, making it show great potential in high-performance applications. The physicochemical properties of IL-functionalized Silicalite-1@SiO2 nanoparticles can be adjusted by controlling the synthesis conditions to meet different application requirements.

[0006] This patent selects Pebax-1657 as the membrane matrix. Pebax-1657 is copolymerized by 40wt% PA and 60wt% PE. This model is selected because it has certain mechanical strength and good adsorption performance for CO2. The high specific surface area of ​​Silicalite-1@SiO2 particles as fillers provides abundant active sites for CO2 gas molecules, enhances the interaction with gas molecules, and thus improves the gas adsorption capacity; at the same time, the molecular sieve characteristics of Silicalite-1 enable it to selectively adsorb or separate according to the size and shape of the molecules, and the surface modified SiO2 can enhance the bonding with the polymer matrix through hydrogen bonds or van der Waals forces. This not only increases the reaction active sites, but also improves the reaction and separation efficiency. A uniform phase interface is formed between the filler and the matrix, and the filler can effectively participate in the gas separation process. The dissolution and adsorption of CO2 in ionic liquids are mainly achieved through physical adsorption, and the physical adsorption process depends on the solubility of ionic liquids and the polarity of CO2 molecules. Generally, the polarity of the anion [BF4]- in 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4] is relatively strong, and it has a strong van der Waals interaction with the CO2 molecule, so that CO2 can be more stably dissolved in the ionic liquid, thereby achieving selective capture; the functionalization of the surface of the ionic liquid functionalized Silicalite-1@SiO2 can improve the selectivity for specific gases and adjust the interaction force with the target gas molecules; the mixed matrix membrane prepared with the ionic liquid functionalized Silicalite-1@SiO2 as filler can overcome the equilibrium effect to a certain extent, thereby improving the separation performance of the membrane; the present invention introduces the ionic liquid functionalized Silicalite-1@SiO2 with CO2 adsorption performance into Pebax-1657 by blending, and Pebax-1657 and the ionic liquid functionalized Silicalite-1@SiO2 have good interface compatibility, thereby solving the problem of low permeability and selectivity of the membrane material to CO2 / N2. Its CO2 permeability (PCO2) can reach 83.43~115.64 Barrer, while the CO2 / N2 selectivity can reach 57.24~78.28.

[0007] In order to solve the above technical problems, the present invention provides a method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane, which is as follows:

[0008] A method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane comprises the following steps:

[0009] Step 1, placing Pebax-1657 and ethanol aqueous solution in a flask, and placing in an oil bath at 60-80° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7-32;

[0010] Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it into the lining of a hydrothermal reactor, adding 2 to 20 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 130 to 150° C. for 4 to 10 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:0.8 to 5;

[0011] Step 3, add Silicalite-1 and ethanol in a round-bottom flask in a mass ratio of 1:10-100, ultrasonicate for 30-60 minutes, add a mixed solution of tetraethyl orthosilicate and ethanol, heat at 60-80°C at a speed of 400-600r / min for 1-2 hours, add 1-butyl-3-methylimidazolium tetrafluoroborate and continue heating for 5-10 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 20-30°C for 12-20 hours, put the product into a vacuum drying oven at 150°C and dry it for 6-12 hours to obtain the target product ionic liquid functionalized Silicalite-1@SiO2 white powder, the above raw materials are calculated by mass ratio, Silicalite-1: tetraethyl orthosilicate: 1-butyl-3-methylimidazolium tetrafluoroborate: concentrated hydrochloric acid = 1:2-5:3-6:7-11;

[0012] Step 4: Functionalize Silicalite-1@SiO with ionic liquid 2加入 In ethanol, the mass ratio is 1:10-50, ultrasonic dispersion is performed for 2-4 hours, stirring at 400-600 r / min for 24-36 hours to obtain ionic liquid functionalized Silicalite-1@SiO2 filler casting solution;

[0013] Step 5. Add Pebax-1657 solution into a reagent bottle, drop ionic liquid functionalized Silicalite-1@SiO2 filler casting solution into it, oscillate using a turbine oscillator for 2 to 4 hours and ultrasonically treat for 10 to 20 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, place it in a constant temperature oven at 60 to 80°C and dry it for 18 to 24 hours, then place it in a vacuum oven and continue to remove the solvent for 10 to 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

[0014] Furthermore, in the mixed solution of tetraethyl orthosilicate and ethanol in step 3, the mass ratio of tetraethyl orthosilicate to ethanol is 1:1-5.

[0015] Furthermore, the mass ratio of ethanol to water in the ethanol aqueous solution in step 3 is 6-9:1-4.

[0016] Furthermore, the mass ratio of the Pebax-1657 solution in step 5 to the ionic liquid functionalized Silica lite-1@SiO2 filler casting solution is 4 to 20:1.

[0017] Furthermore, according to the method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane according to any one of claims 1 to 4, the mixed matrix membrane prepared by the present invention is used for CO2 / N2 gas separation.

[0018] The present invention provides a method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane, wherein the mixed matrix membrane is prepared by blending Pebax-1657 as a matrix material and ionic liquid functionalized Silicalite-1@SiO2 nanoparticle filler, thereby effectively improving the dissolution selectivity of the membrane material for CO2 gas.

[0019] The ionic liquid functionalized Silicalite-1@SiO2 composite is a core-shell structure material, in which SiO2 is formed on the outer layer of Silicalite-1 nanoparticles. This structure is obtained by direct synthesis in a eutectic mixture, in which amorphous SiO2 is converted into an MFI-type structure and is coated by amorphous SiO2. In this structure, the Silicalite-1 grains grow in situ, and their physicochemical properties are strongly affected by alkalinity, template agent and crystallization time. By controlling these factors, the physicochemical properties of SiO2@Silicalite-1 can be adjusted. The formation process of this composite follows the in situ epitaxial growth and phase transition mechanism. The high specific surface area of ​​SiO2 nanoparticles provides abundant active sites for gas molecules, enhances the interaction with gas molecules, and thus improves the gas adsorption capacity, which is crucial to improve the gas separation efficiency. At the same time, the molecular sieve properties of Silicalite-1 enable it to selectively adsorb or separate according to the size and shape of the molecules, which not only increases the reactive active sites, but also improves the reaction and separation efficiency. In addition, the dissolution and adsorption of CO2 in ionic liquids are mainly achieved through physical adsorption, which depends on the solubility of ionic liquids and the polarity of CO2 molecules. Due to the strong polarity of anions in ionic liquids, the van der Waals interaction between them and CO2 molecules is more significant, which enables CO2 to dissolve more stably in ionic liquids and achieve selective capture of CO2. Therefore, ionic liquid functionalized Silicalite-1@SiO2 composite materials not only perform well in gas adsorption and separation, but also have important application potential in improving reaction efficiency and selectivity. The mixed matrix membrane prepared with ionic liquid functionalized Silicalite-1@SiO2 as filler has a CO2 permeability (PCO2) of 83.43 to 115.64 Barrer, and the CO2 / N2 selectivity reaches 57.24-78.28. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Sample diagram of the synthesis process of Silicalite-1 (left picture is 1 hour, right picture is 6 hours);

[0021] Figure 2 The X-ray diffraction patterns of the mixed matrix membranes of Comparative Example 1 and Examples 1 to 4;

[0022] Figure 3 X-ray diffraction patterns of the Silicalite-1@Pebax-1657 mixed matrix membrane of Comparative Example 2 and the Silicalite-1 nanocrystals synthesized in Comparative Examples 3 and 4;

[0023] Figure 4It is a performance diagram of the mixed matrix membrane of Examples 1 to 4 and Comparative Examples 1 to 2. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] The following is a specific description of the preparation method of an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane provided by the present invention through examples.

[0026] The materials used in the following examples were all purchased from the market, wherein Pebax-1657 was purchased from Arkema, France; tetrapropylammonium hydroxide (TPAOH) was purchased from Aladdin Chemical Co., Ltd., USA; 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4] was purchased from Aladdin Chemical Co., Ltd., USA; and tetraethyl orthosilicate (TEOS) was purchased from Aladdin Chemical Co., Ltd., USA.

[0027] Embodiment 1:

[0028] Step 1, Pebax-1657 and ethanol aqueous solution are placed in a flask, and oil bathed at 60° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7;

[0029] Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding 5 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 135° C. for 6 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:1;

[0030] Step 3, add Silicalite-1 and ethanol in a mass ratio of 1:10 to a round-bottom flask, add a mixed solution of tetraethyl orthosilicate and ethanol after ultrasonication for 30 minutes, heat at 60°C for 2 hours at a speed of 400r / min, add 1-butyl-3-methylimidazolium tetrafluoroborate and continue heating for 5 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 25°C for 12 hours, put the product into a vacuum drying oven at 150°C and dry it for 6 hours to obtain a white powder target product ionic liquid functionalized Silicalite-1@SiO2, the above raw materials are calculated by mass ratio, Silicalite-1:tetraethyl orthosilicate:1-butyl-3-methylimidazolium tetrafluoroborate:concentrated hydrochloric acid=1:2:3:7;

[0031] Step 4: Functionalize the prepared ionic liquid into Silicalite-1@SiO 2加入 The mass ratio of the two in ethanol was 1:10, ultrasonic dispersion was performed for 2 hours, and stirring was performed at 400 r / min for 24 hours to obtain the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution;

[0032] Step 5. Add the Pebax-1657 solution into the reagent bottle, drop the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution (mass ratio of 19:1) into it, oscillate using a turbine oscillator for 2 hours and ultrasonically treat for 10 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, put it in a constant temperature oven at 60°C and dry it for 24 hours, and then put it in a vacuum oven at 60°C and dry it for 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

[0033] exist Figure 2 In the XRD spectrum of the prepared Silicalite-1@SiO2 mixed matrix membrane, a small peak appears at 2θ of 23.99°, proving that the prepared mixed matrix membrane contains Silicalite-1 nanocrystals. The unclear peak position also proves that the outer layer of the Silicalite-1 nanocrystals is grown with SiO2 and impregnated with ionic liquid.

[0034] After testing, the ionic liquid functionalized Silicalite-1@SiO2 content of the above-mentioned mixed matrix membrane is 5wt.% MMMs, which exhibits CO2 permeability coefficient and CO2 / N2 selectivity. The CO2 permeability coefficient is 83.43 Barrer, and the CO2 / N2 selectivity is 71.55, which has good CO2 permeability and excellent CO2 / N2 selectivity.

[0035] Embodiment 2:

[0036] Step 1, Pebax-1657 and ethanol aqueous solution are placed in a flask, and oil bathed at 60° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7;

[0037] Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding 5 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 135° C. for 6 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:1;

[0038] Step 3, add Silicalite-1 and ethanol in a mass ratio of 1:10 to a round-bottom flask, add a mixed solution of tetraethyl orthosilicate and ethanol after ultrasonication for 30 minutes, heat at 60°C for 2 hours at a speed of 400r / min, add 1-butyl-3-methylimidazolium tetrafluoroborate and continue heating for 5 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 25°C for 12 hours, put the product into a vacuum drying oven at 150°C and dry it for 6 hours to obtain a white powder target product ionic liquid functionalized Silicalite-1@SiO2, the above raw materials are calculated by mass ratio, Silicalite-1:tetraethyl orthosilicate:1-butyl-3-methylimidazolium tetrafluoroborate:concentrated hydrochloric acid=1:2:3:7;

[0039] Step 4: Functionalize the prepared ionic liquid into Silicalite-1@SiO 2加入 The mass ratio of the two in ethanol was 1:10, ultrasonic dispersion was performed for 2 hours, and stirring was performed at 400 r / min for 24 hours to obtain the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution;

[0040] Step 5. Add the Pebax-1657 solution into the reagent bottle, drop the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution (mass ratio of 9:1) into it, oscillate using a turbine oscillator for 2 hours and ultrasonically treat for 10 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, put it in a constant temperature oven at 60°C and dry it for 24 hours, and then put it in a vacuum oven at 60°C and dry it for 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

[0041] exist Figure 2In the XRD spectrum of the prepared Silicalite-1@SiO2 mixed matrix membrane, a small peak appears at 2θ of 23.99°, proving that the prepared mixed matrix membrane contains Silicalite-1 nanocrystals. The unclear peak position also proves that the outer layer of the Silicalite-1 nanocrystals is grown with SiO2 and impregnated with ionic liquid.

[0042] After testing, the mixed matrix membrane with a content of 10wt.% MMMs showed the best CO2 permeability coefficient ionic liquid functionalized Silicalite-1@SiO2 and CO2 / N2 selectivity, with a CO2 permeability coefficient of 98.67 Barrer and a CO2 / N2 selectivity of 78.28, and has good CO2 permeability and excellent CO2 / N2 selectivity.

[0043] Embodiment 3:

[0044] Step 1, Pebax-1657 and ethanol aqueous solution are placed in a flask, and oil bathed at 60° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7;

[0045] Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding 5 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 135° C. for 6 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:1;

[0046] Step 3, add Silicalite-1 and ethanol in a mass ratio of 1:10 to a round-bottom flask, add a mixed solution of tetraethyl orthosilicate and ethanol after ultrasonication for 30 minutes, heat at 60°C for 2 hours at a speed of 400r / min, add 1-butyl-3-methylimidazolium tetrafluoroborate and continue heating for 5 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 25°C for 12 hours, put the product into a vacuum drying oven at 150°C and dry it for 6 hours to obtain a white powder target product ionic liquid functionalized Silicalite-1@SiO2, the above raw materials are calculated by mass ratio, Silicalite-1:tetraethyl orthosilicate:1-butyl-3-methylimidazolium tetrafluoroborate:concentrated hydrochloric acid=1:2:3:7;

[0047] Step 4: Functionalize the prepared ionic liquid into Silicalite-1@SiO 2加入The mass ratio of the two in ethanol was 1:10, ultrasonic dispersion was performed for 2 hours, and stirring was performed at 400 r / min for 24 hours to obtain the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution;

[0048] Step 5. Add the Pebax-1657 solution into the reagent bottle, drop the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution (mass ratio of 5.7:1) into it, oscillate using a turbine oscillator for 2 hours and ultrasonically treat for 10 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, put it in a constant temperature oven at 60°C and dry it for 24 hours, and then put it in a vacuum oven at 60°C and dry it for 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

[0049] exist Figure 2 In the XRD spectrum of the prepared Silicalite-1@SiO2 mixed matrix membrane, the XRD spectrum shows a small peak at 2θ of 23.99°, proving that the prepared mixed matrix membrane contains Silicalite-1 nanocrystals. The peak position is not obvious, which also proves that the outer layer of the Silicalite-1 nanocrystals has SiO2 and is impregnated with ionic liquids. The peak position is slightly lower than that of Example 2 because a high content of filler will cause the particles to aggregate more easily in the matrix rather than be evenly dispersed, resulting in randomization of the crystal orientation, thereby weakening the XRD diffraction peak intensity of a specific crystal plane and reducing the peak position of the characteristic peak. It can be seen from Table 1 that the selectivity of Example 3 is lower than that of Example 2, which may also be due to its particle agglomeration phenomenon.

[0050] After testing, the mixed matrix membrane with a content of 15wt.% MMMs showed good CO2 permeability coefficient ionic liquid functionalized Silicalite-1@SiO2 and CO2 / N2 selectivity, with a CO2 permeability coefficient of 103.39 Barrer and a CO2 / N2 selectivity of 68.93.

[0051] Embodiment 4:

[0052] Step 1, Pebax-1657 and ethanol aqueous solution are placed in a flask, and oil bathed at 60° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7;

[0053] Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it to the lining of a hydrothermal reactor, adding 5 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 135° C. for 6 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:1;

[0054] Step 3, add Silicalite-1 and ethanol in a round-bottom flask in a mass ratio of 1:10, ultrasonicate for 30 minutes, add a mixed solution of tetraethyl orthosilicate and ethanol, heat at 60°C for 2 hours at a speed of 400r / min, add 1-butyl-3-methylimidazolium tetrafluoroborate, continue heating for 5 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 20-30°C for 12 hours, put the product in a vacuum drying oven at 150°C and dry for 6 hours to obtain a white powder target product ionic liquid functionalized Silicalite-1@SiO2. The above raw materials are calculated by mass ratio: Silicalite-1: tetraethyl orthosilicate: 1-butyl-3-methylimidazolium tetrafluoroborate: concentrated hydrochloric acid = 1:2:3:7;

[0055] Step 4: Functionalize the prepared ionic liquid into Silicalite-1@SiO 2加入 The mass ratio of the two in ethanol was 1:10, ultrasonic dispersion was performed for 2 hours, and stirring was performed at 400 r / min for 24 hours to obtain the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution;

[0056] Step 5. Add the Pebax-1657 solution into the reagent bottle, drop the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution (mass ratio of 4:1) into it, oscillate using a turbine oscillator for 2 hours and ultrasonically treat for 10 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, put it in a constant temperature oven at 60°C and dry it for 24 hours, and then put it in a vacuum oven at 60°C and dry it for 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

[0057] exist Figure 2In the XRD spectrum of the prepared Silicalite-1@SiO2 mixed matrix membrane, the XRD spectrum shows a small peak at 2θ of 23.99°, proving that the prepared mixed matrix membrane contains Silicalite-1 nanocrystals. The peak position is not obvious, which also proves that the outer layer of the Silicalite-1 nanocrystals is grown with SiO2 and impregnated with ionic liquids. The peak position is lower than that of Example 3 because the high content of filler will cause the particles to aggregate more easily in the matrix rather than be evenly dispersed, resulting in randomization of the crystal orientation, thereby weakening the XRD diffraction peak intensity of a specific crystal plane and reducing the peak position of the characteristic peak. It can be seen from Table 1 that the selectivity of Example 4 is lower than that of other examples, which also indirectly confirms this theory.

[0058] The content of the mixed matrix membrane was 20wt.% MMMs, which showed good CO2 permeability coefficient and CO2 / N2 selectivity. The CO2 permeability coefficient was 115.64 Barrer and the CO2 / N2 selectivity was 58.34.

[0059] Comparative Example 1:

[0060] Preparation of pure Pebax-1657 mixed matrix membranes:

[0061] Pebax-1657:ethanol in a mass ratio of 1:7 was placed in a flask in an oil bath at 60°C for 4 hours to obtain a Pebax solution of uniform concentration. The solution was then ultrasonically degassed for 10 minutes and allowed to stand for 10 minutes before being poured into a clean polytetrafluoroethylene mold. The membrane was then placed in a constant temperature oven and dried at 60°C for 24 hours. Finally, the membrane was evacuated in a vacuum oven and dried at 60°C for 12 hours to obtain a pure Pebax-1657 mixed matrix membrane.

[0062] exist Figure 3 In the XRD pattern, the prepared pure Pebax-1657 mixed matrix membrane has a non-crystalline structure, so no characteristic peaks appear.

[0063] The separation performance of the mixed matrix membrane was tested to be P CO2 =65.98 Barrer, CO2 / N2 selectivity 57.24.

[0064] Comparative Example 2:

[0065] Preparation of Silicalite-1 / Pebax-1657 mixed matrix membrane

[0066] Pebax-1657:ethanol (mass ratio 1:7) was placed in a flask and placed in an oil bath at 60°C for 4 hours to obtain a Pebax solution of uniform concentration. The Pebax-1657 solution was weighed into a reagent bottle, and 10 wt.% casting liquid was dropped therein (the Silicalite-1 nanocrystals prepared in Comparative Example 3 were added to ethanol, ultrasonicated for 2 hours, and then placed on a stirring table and stirred for more than 24 hours to obtain a Silicalite-1 filler casting liquid). The mixture was oscillated on a turbine oscillator for 4 hours and ultrasonicated for 10 minutes. After the filler and the polymer solution were evenly mixed, the casting liquid was statically degassed. The prepared mixed matrix membrane solution was poured onto a polytetrafluoroethylene plate, placed in a constant temperature oven at 60°C and dried for 24 hours, and then placed in a vacuum oven at 60°C and vacuumed to continue to remove the solvent for 12 hours to obtain a Silicalite-1 / Pebax mixed matrix membrane.

[0067] exist Figure 3 In the XRD spectrum of the prepared Silicalite-1 / Pebax mixed matrix membrane, the XRD spectrum showed small peaks at 2θ of 7.96°, 8.83°, 23.99°, and 24.45°, proving that the prepared mixed matrix membrane contained Silicalite-1 nanocrystals.

[0068] The separation performance of the mixed matrix membrane was tested to be P CO2 =75.26 Barrer, CO2 / N2 selectivity 58.08.

[0069] Comparative Example 3:

[0070] Synthesis of Silicalite-1 by crystallization using TPAOH as a template for 6 hours

[0071] Weigh white carbon black and tetrapropylammonium hydroxide in a mass ratio of 1:1, stir under the action of a solvent until the tetrapropylammonium hydroxide is fully dissolved, then add white carbon black, transfer to a reactor, age at room temperature for 2 hours, then transfer the reactor to a 135°C oven for reaction for 6 hours, centrifuge washing, dry, and calcine to obtain a dry Silicalite-1 filler.

[0072] exist Figure 3 In the XRD spectrum of the prepared Silicalite-1 nanocrystals, the XRD characteristic peaks of the prepared Silicalite-1 nanocrystals appeared at 2θ of 7.96°, 8.83°, 23.18°, 23.99°, and 24.45°, which were Silicalite-1 nanocrystals, and the baseline was flat, indicating that the Silicalite-1 seed crystals had good crystallinity.

[0073] Comparative Example 4:

[0074] Synthesis of Silicalite-1 by crystallization using TPAOH as a template for 1 hour

[0075] Weigh white carbon black and tetrapropylammonium hydroxide in a mass ratio of 1:1, stir under the action of a solvent until the tetrapropylammonium hydroxide is fully dissolved, then add white carbon black, transfer to a reactor, age at room temperature for 2 hours, then transfer the reactor to a 135°C oven for reaction for 1 hour, centrifuge washing, dry, and calcine to obtain a dry Silicalite-1 filler.

[0076] exist Figure 3 In the XRD spectrum, the prepared Silicalite-1 filler does not show obvious characteristic peaks, but shows a broad, diffusely scattered peak. This indicates that the atomic arrangement of the measured sample lacks long-range order and presents typical amorphous structural characteristics.

[0077] The peak shape of the XRD spectrum of Silicalite-1 is amorphous, indicating that the product is not crystallized.

[0078] Comparative Examples 1 to 2 Examples 1 to 4 and the prepared ionic liquid functionalized Silicalite-1@SiO2-Pebax-1657 mixed matrix membrane, the distribution ratio of each group, the CO2 permeability coefficient (Barrer), i.e., the CO2 / N2 selectivity test results are shown in Table 1.

[0079] Table 1

[0080] Filler content (wt%) <![CDATA[CO2 Permeability Coefficient (Barrer)]]> <![CDATA[CO2 / N2 selectivity]]> Comparative Example 1 0 65.98 57.24 Comparative Example 2 10 75.26 58.08 Example 1 5 83.43 71.55 Example 2 10 98.67 78.28 Example 3 15 103.39 68.93 Example 4 20 115.64 58.34

[0081] Conclusion: From Table 1 and Figure 4 It can be seen from the performance diagram that the CO2 permeability coefficient and CO2 / N2 selectivity of Examples 1 to 4 of the present invention are better than those of Comparative Examples 1 to 2. When the content of ionic liquid functionalized Silicalite-1@SiO2 in Example 2 is 10 wt.%, the CO2 permeability coefficient can reach 98.67 Barrer and the CO2 / N2 selectivity is 78.28, which has good permeability and selectivity.

[0082] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be obvious to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited.

Claims

1. A method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane, characterized in that: The following steps are involved: Step 1, placing Pebax-1657 and ethanol aqueous solution in a flask, and placing in an oil bath at 60-80° C. for 4 hours to obtain a Pebax solution of uniform concentration, wherein the mass ratio of Pebax-1657 to ethanol aqueous solution is 1:7-32; Step 2, mixing white carbon black and tetrapropylammonium hydroxide to obtain a mixture, adding the mixture into an open glass container, and transferring it into the lining of a hydrothermal reactor, adding 2 to 20 mL of deionized water outside the mouth of the glass bottle in the lining, subjecting the encapsulated hydrothermal reactor to crystallization treatment at 130 to 150° C. for 4 to 10 hours to obtain a crystalline product, centrifuging, washing, drying, and calcining the product to obtain Silicalite-1 nanocrystals, wherein the mass ratio of white carbon black to tetrapropylammonium hydroxide is 1:0.8 to 5; Step 3, add Silicalite-1 and ethanol in a round-bottom flask in a mass ratio of 1:10-100, ultrasonicate for 30-60 minutes, add a mixed solution of tetraethyl orthosilicate and ethanol, heat at 60-80°C at a speed of 400-600r / min for 1-2 hours, add 1-butyl-3-methylimidazolium tetrafluoroborate and continue heating for 5-10 hours, add concentrated hydrochloric acid dropwise until a gel state appears, stop stirring, age at 20-30°C for 12-20 hours, put the product into a vacuum drying oven at 150°C and dry it for 6-12 hours to obtain the target product ionic liquid functionalized Silicalite-1@SiO2 white powder, the above raw materials are calculated by mass ratio, Silicalite-1: tetraethyl orthosilicate: 1-butyl-3-methylimidazolium tetrafluoroborate: concentrated hydrochloric acid = 1:2-5:3-6:7-11; Step 4: Functionalize Silicalite-1@SiO with ionic liquid 2加入 In ethanol, the mass ratio is 1:10-50, ultrasonic dispersion is performed for 2-4 hours, stirring at 400-600 r / min for 24-36 hours to obtain ionic liquid functionalized Silicalite-1@SiO2 filler casting solution; Step 5. Add Pebax-1657 solution into a reagent bottle, drop ionic liquid functionalized Silicalite-1@SiO2 filler casting solution into it, oscillate using a turbine oscillator for 2 to 4 hours and ultrasonically treat for 10 to 20 minutes. After the filler and the polymer solution are evenly mixed, the casting solution is statically degassed; pour the prepared mixed matrix membrane solution onto a polytetrafluoroethylene plate, place it in a constant temperature oven at 60 to 80°C and dry it for 18 to 24 hours, and then place it in a vacuum oven at 50 to 80°C and dry it for 10 to 12 hours to obtain a mixed matrix membrane of ionic liquid functionalized Silicalite-1@SiO2.

2. The method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane according to claim 1, characterized in that: In step 3, the mixed solution of tetraethyl orthosilicate and ethanol has a mass ratio of tetraethyl orthosilicate to ethanol of 1:1 to 5.

3. The method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane according to claim 1, characterized in that: The mass ratio of ethanol to water in the ethanol aqueous solution in step 1 is 6-9:1-4.

4. The method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane according to claim 1, characterized in that: In step 5, the mass ratio of the Pebax-1657 solution to the ionic liquid functionalized Silicalite-1@SiO2 filler casting solution is 4 to 20:

1.

5. A method for preparing an ionic liquid functionalized Silicalite-1@SiO2 mixed matrix membrane according to any one of claims 1 to 4, characterized in that: The mixed matrix membrane prepared by the invention is used for CO2 / N2 gas separation.

Citation Information

Patent Citations

  • Ionic liquid modified mesoporous molecular sieve / polymer composite film and preparation and application thereof

    CN105642130A

  • Method for rapid synthesis of mesoporous Silicalite-1 molecular sieves by taking white carbon black as silicon source

    CN105645425A

  • Silicalite-1 molecular sieve membrane preparation method

    CN109569316A

  • Facilitated transport membranes for carbon dioxide separation using ionic liquids in nanoporous materials

    KR1020160011473A